2007
DOI: 10.1097/01.ta.0000249129.63550.cc
|View full text |Cite
|
Sign up to set email alerts
|

Incidental CT Findings in Trauma Patients: Incidence and Implications for Care of the Injured

Abstract: SCT for the evaluation of trauma patients reveals a significant number of incidental findings. These lesions are common in the abdomen and pelvis and show an increased incidence in women and among older patients. Although many require early follow-up and specialty physician referral, there was insufficient documentation of the management of these injuries. Incidental findings in the injured remain a significant challenge for trauma centers. An organized approach is required for successful follow-up and managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 11 publications
12
128
2
1
Order By: Relevance
“…Our finding of a rate of incidental findings of 33.4% is similar to that found in previous studies [4,5]. However, the rate we observed in abdominal CT scans (56.3%) was higher even than the highest rate previously reported (45%) [8].…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Our finding of a rate of incidental findings of 33.4% is similar to that found in previous studies [4,5]. However, the rate we observed in abdominal CT scans (56.3%) was higher even than the highest rate previously reported (45%) [8].…”
Section: Discussioncontrasting
confidence: 42%
“…While some of these incidental findings are benign and require no followup, others require serial imaging and close supervision of the patient by their primary care physician [3]. Prior studies have examined rates of incidental findings in trauma patients, a group that receives large amounts of CT scans in their workup [4][5][6][7], and renal colic patients [8]. Rates of incidental findings varied from 34% to 43% on abdominal CT scans in trauma patients [4][5][6], and up to 45% in renal colic ED patients [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are plenty of studies evaluating incidental findings on CTs of trauma patients, but those include mainly thoracic, abdominal and cranial abnormalities. [2][3][4][5][6][7] To the best of our knowledge, there is just one study in the literature where the incidental cervical CT findings of trauma patients were regularly evaluated. 8 In this study, mainly osseous abnormalities and traumatic soft-tissue abnormalities were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of trauma patients with incidental findings detected on imaging have confirmed lower rates of both documentation (15-48%) and follow-up (49%) (27,28). This is likely due to poor communication between health care systems as well as between providers and patients.…”
Section: Strengths and Limitationsmentioning
confidence: 98%